Microbial Utilisation of Aboveground Litter-Derived Organic Carbon Within a Sandy Dystric Cambisol Profile - Preusser, Sebastian; Liebmann, Patrick; Stucke, Andres; Wirsching, Johannes; Müller, Karolin; Mikutta, Robert; Guggenberger, Georg; Don, Axel; Kalbitz, Karsten; Bachmann, Jörg; Marhan, Sven; Poll, Christian; et al. (Frontiers in Soil Science, 2021)
Litter-derived dissolved organic carbon (DOC) is considered to be a major source of stabilized C in soil. Here we investigated the microbial utilization of litter-derived DOC within an entire soil profile using a stable isotope labelling experiment in a temperate beech forest. The natural litter layer of a Dystric Cambisol was replaced by 13C enriched litter within three areas of each 6.57 m-2 for 22 months and then replaced again by natural litter (switching-off the 13C input). Samples were taken continuously from 0 to 180 cm depths directly after the replacement of the labelled litter, and 6 and 18 months thereafter. We followed the pulse of 13C derived from aboveground litter into soil microorganisms through depth and over time by analysing 13C incorporation into microbial biomass and phospholipid fatty acids. Throughout the sampling period, most of the litter-derived microbial C was found in the top cm of the profile and only minor quantities were translocated to deeper soil. The microbial 13C stocks below 30 cm soil depth at the different samplings accounted constantly for only 6-12% of the respective microbial 13C stocks of the entire profile. The peak in proportional enrichment of 13C in subsoil microorganisms moved from upper (≤ 80 cm soil depth) to lower subsoil (80-160 cm soil depth) within a period of six months after switch-off, and nearly disappeared in microbial biomass after 18 months (< 1%), indicating little long-term utilization of litter-derived C by subsoil microorganisms. Among the different microbial groups, a higher maximum proportion of litter-derived C was found in fungi (up to 6%) than in bacteria (2%), indicating greater fungal than bacterial dependency on litter-derived C in subsoil. However, in contrast to topsoil, fungi in subsoil had only a temporarily restricted increase in litter C incorporation, while in the Gram-positive bacteria, the C incorporation in subsoil raised moderately over time increasingly contributing to the group-specific C stock of the entire profile (up to 9%). Overall, this study demonstrated that microorganisms in topsoil of a Dystric Cambisol process most of the recently deposited aboveground litter C, while microbial litter-derived C assimilation in subsoil is low.